DOP63 Efficacy and safety of iron carboxymaltose on chronic fatigue in patients with inflammatory bowel disease: a randomised controlled trial. (15th January 2020) - Fiorino, G; Allocca, M; Gilardi, D; Alfieri, M; Danieli, P; Furfaro, F; Roda, G; Loy, L; Zilli, A; Radice, S; Peyrin-Biroulet, L; Danese, S
Abstract: Background: Patients with inflammatory bowel diseases (IBD) have an altered quality of life, also due to chronic fatigue (CF). Iron administration is effective in iron deficiency associated with CF in patients with heart failure. Our hypothesis was that iron administration in patients with iron-deficiency could improve CF and quality of life in IBD patients. Methods: This was a phase 2, randomised, placebo-controlled, double-blind trial. Adult patients with established IBD diagnosis in clinical remission (HB <5; Mayo clinical score ≤2) from ≥ 6 months, CF symptoms (MFI-20> 13), martial deficiency (ferritin <100 µg/l, or <300 µg/l if transferrin saturation<20%), but not anaemia, were eligible. Patients were randomised to receive 200 mg of i.v. iron carboxymaltose (ICM) or placebo (PBO) every month up to 6 months. The primary objective was to compare the rate of patients in CF remission (Multidimensional Fatigue Inventory, MFI-20 <13) between the 2 groups. Secondary objectives were CF response (MFI-20 decrease of ≥4 points, but MFI-20 total >13) at week 24 and CF remission (MFI-20 <13) at week 12. Evolution of anxiety and depression and change in the quality of life at weeks 4, 12 and 24 from baseline trough week 24 were also assessed. The calculated sample size was 36 patients (18 for each treatment arm). Results: Forty-six patients were screened, 30 patients completed 24 weeks of treatment (21 Crohn's disease, 9 ulcerative colitis). Baseline characteristics were not different among the two groups. Between patients treated with ICM vs. PBO, 2/15 patients vs. 0/15 respectively were in CF remission at week 24 (13% vs. 0%, p = 0.46). CF response was observed in 7/15 patients treated with ICM vs. 10/15 patients with PBO (47% vs. 67%, p = 0.46). At week 12, 1/17 vs. 0/17 patients were in CF remission (6% vs. 0%, p = 0.96), and 12/17 vs. 10/17 (71% vs. 59%, p = 0.90) showed CF response. At the study completion, ferritin restoration was found in 12/14 patients (86%) treated with ICM vs. 1/15 (7%) receiving PBO ( p < 0.001). No significant differences in terms of anxiety, depression and quality of life restoration were found between the two groups at week 12 and 24. A total number of 69 adverse events (AEs) were reported in 17 patients (37 mild, 31 moderate, 1 severe), only 5 were related to the study treatment (3 nausea, 1 gastric pain, 1 arthralgia), and only 1 (nausea) led to study drug discontinuation. Conclusion: Intravenous ICM is not effective in treating CF in IBD patients, with no significant adverse events. ICM was more effective than PBO in restoring ferritin in the majority of IBD patients. Funding: This study was funded by the ECCO Vifor Grant 2017.